2015
DOI: 10.1111/hpb.12485
|View full text |Cite
|
Sign up to set email alerts
|

Survival outcomes in liver transplant recipients with Model for End‐stage Liver Disease scores of 40 or higher: a decade‐long experience

Abstract: Liver transplantation in recipients with MELD scores of ≥40 offers acceptable longterm survival outcomes. Futility predictors indicate the need for prospective follow-up studies to define the population to gain the highest benefit from this precious resource.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 12 publications
(42 reference statements)
0
29
0
Order By: Relevance
“…In recent years, the notion of "futility" of LT has been used if post-transplant mortality was higher than waiting list mortality 81,82 or in case of 3month or in-hospital mortality after LT. 76,83 However, authors of a recent review preferred to correct "futile" LT to "potentially inappropriate" LT, thus reducing the value judgment inherent to the term "futile". 80 This semantic change follows the adoption of these new terms by a multisociety statement that provided guidance for clinicians to prevent and manage disputes regarding patients with advanced critical illnesses.…”
Section: Therapiesmentioning
confidence: 99%
“…In recent years, the notion of "futility" of LT has been used if post-transplant mortality was higher than waiting list mortality 81,82 or in case of 3month or in-hospital mortality after LT. 76,83 However, authors of a recent review preferred to correct "futile" LT to "potentially inappropriate" LT, thus reducing the value judgment inherent to the term "futile". 80 This semantic change follows the adoption of these new terms by a multisociety statement that provided guidance for clinicians to prevent and manage disputes regarding patients with advanced critical illnesses.…”
Section: Therapiesmentioning
confidence: 99%
“…These conflicting results, compared to the results of the present study, could be explained by differences in pretransplant patient selection and clinical management, especially for patients with high MELD scores and complex morbidity. Another retrospective longitudinal analysis of United Network for Organ Sharing (UNOS) data on all liver transplantations performed between February 2002 and June 2011, including 33 398 transplant recipients, showed that overall post‐transplant patient survival was inversely correlated with increasing MELD score, but LT in recipients with MELD scores ≥40 achieved acceptable long‐term survival outcomes . Moreover, another recent analysis of UNOS data from 2002 to 2013, based on 50 838 transplant recipients, showed a significant interaction between MELD score and hospitalization status on post‐LT survival.…”
Section: Discussionmentioning
confidence: 99%
“…The following algorithm was used to calculate the MELD score: MIN (40,ROUND(10*(0.957*LOG(MIN(MAX (0.0113*CREAT,1),4)) + 0.378*LOG(MAX (0.06*BILI,1)) + 1.12*LOG(MAX(INR,1)) + 0.643))). The MELD score was categorized into 6 different groups of severity: <15, [15][16][17][18][19][20], [20][21][22][23][24][25]…”
Section: Data Collection and Variables Recordedmentioning
confidence: 99%
“…In the era of high‐acuity liver transplantation, there is a need to evaluate those factors that negatively contribute to overall graft and patient survival because patient selection remains a critical determinant of OLT outcomes. Although previous studies have evaluated age, sepsis, cardiac risk, and extreme MELD as potential predictors of poor outcomes, a similar assessment has never been undertaken to assess acute pancreatitis, which occurs in 1.5%‐3.0% of liver transplant patients . Previous studies of pancreatitis among liver transplant patients have demonstrated its association with acute liver failure and hepatitis B virus in the preoperative setting, and with interventional procedures (such as ERCP) in the postoperative setting .…”
Section: Discussionmentioning
confidence: 99%